In vitro adhesion of Escherichia coli to porcine small intestinal epithelial cells: pili as adhesive factors. - Isaacson, R E (1978)
Escherichia coli strains with pili (K99 or 987P) known to facilitate intestinal colonization adhered in vitro to porcine intestinal epithelial cells. These strains adhered equally to both ileal and jejunal epithelial cells. A laboratory E. coli strain that has type 1 pili also adhered to porcine intestinal epithelial cells. When nonpiliated cells derived from 987P+, K99+, or type 1 pilus+ strains were used for in vitro adhesion assays, they failed to adhere. The attachment of piliated bacteria to epithelial cells was a saturable process that plateaued at 30 to 40 bacterial cells attached per epithelial cell. Competitive inhibition of bacterial cell attachment to epithelial cells with purified pili showed that only purified 987P competed against the 987P+ strain and only purified type 1 pili competed against the type 1 pilus+ strain. Competition between a K99+ strain and K99 was not consistently achieved. K99+, 987P+, and type 1 pilus+ bacteria could be prevented from adhering to epithelial cells by Fab fragments specific for K99, 987P, or type 1 pili, respectively. Fab fragments specific for non-K99 bacterial surface antigens did not inhibit adhesion of the K99+ strain. It is concluded that adhesion of E. coli to porcine intestinal epithelial cells in vitro is mediated by pili and that the epithelial cells used apparently had different receptors for different pili.